CHAVEIRO, EGUIMAR FELÍCIO; CALAÇA, MANOEL; REZENDE, MÔNICA CRISTINA DA SILVA: A DINÂMICA DEMOGRÁFICA DE GOIÁS. GOIÂNIA: ED. ELLOS, 2009. 129 P. - Borges Alencar Rusel, Andréia (Boletim Goiano de Geografia, 2010)
.